Using reconditioned pacemakers to treat bradycardia in Africa. Issue 12 (December 2018) - Wunderly, Kevin; Yousef, Zaheer; Bonny, Aimé; Weatherwax, Kevin; Lavan, Balasundaram; Allmendinger, Craig; Wasserman, Brad; Samson, George; Davis, Sheldon; Nel, George; Russell, James; Akwanalo, Constantine; et al.
Pacemaker therapy is inaccessible to most patients with bradycardia in Africa. Use of reconditioned pacemakers has been proposed as a safe, efficacious, and ethical means of delivering this therapy. A collaboration between PASCAR, Pace4Life, and Project My Heart Your Heart is working to address this deficit in health care in Africa.